Jurnal Ekonomi & Bisnis Volume 8, Nomor 1, Juli 2017 - LPPM STIE Port Numbay (Sekolah Tinggi Ilmu Ekonomi Port Numbay Jayapura, 2021)
Journal of Economics and Business Volume 8, Number 1, July 2017 is now present as a means of scientific communication that examines various social phenomena in the form of theoretical studies, social concepts, research results and social applications. Journal of Economics and Business is a journal that is fostered and published by LP2M School of Economics Port Numbay, as a scientific vehicle, intended to accommodate various scientific critical thoughts of academics both in the public and private circles. themselves and outsiders who are interested in contributing writings. Finally, a note that should be informed for interested parties who wish to contribute articles, is urged to try to follow the environmental style of the Journal of Economics and Business.